Perlakuan Akuntansi Sumber Daya Manusia: Assets Sekaligus Investor Bagi Perusahaan - Ningsih, Sri (Journal of Accounting and Investment, 2001)
Human resources or called employee as a company asset to be one determinant of the success of the company (organization). Issue growing is that labor (human resources) is not only the company's assets but also as owners and investors on its human capital to be invested in the company where he works (at work). This article tries to see how human resources can be considered as an asset for the company and when human resources can act as an investor of its human capital. This article also discusses the accounting treatment of human resources as company assets and the possibility of counting on human resources as human capital investor.Â  Â Â